In situ behavioral plasticity as compensation for weather variability: implications for future climate change - Noonan, M; Newman, C; Markham, A; Bilham, K; Buesching, C; Macdonald, D (Springer Netherlands, 2018)
While climatic effects on species biogeographic distributions are well documented, less mobile species must compensate for climate change in situ via behavioral plasticity. Despite this being a critical mechanism, behavioral plasticity is rarely modeled explicitly. Here, we use novel accelerometer and active-RFID transponder technology to quantify weather-driven modification of activity, mechanical energy expenditure, and ranging behavior, using the European badger as a model species. We then examine how these behaviors could respond to future climate change. From multi-model inference, activity was promoted significantly by a quadratic relationship with temperature, but inhibited by a quadratic relationship with humidity, and the amount of solar radiation. Drier conditions also encouraged more movement. Modeled against IPCC SRES low and high emissions climate change scenarios, milder and drier conditions projected for the next century would likely produce a change to badgers’ current phenology, with elevated levels of activity being maintained into the winter. This increased activity could necessitate up to a 15% increase in energy expenditure. Furthermore, conditions projected under the high emissions scenario may also lead to substantially increased movement, with implications for road traffic mortality rates. We contend that behavioral adaptation must be better incorporated into conservation strategies, versus the assumption of non-adaptive failure.